Taizé Meditation as an Intervention to Reduce Anxiety in First-Year Nursing Students - Br. Karo, Mestiana; Ndruru, Tince Maria Hati (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: Taizé meditation is a form of meditative worship that fosters inner peace through repetitive chants and musical prayers. This practice is particularly beneficial for individuals experiencing anxiety. Anxiety itself is characterized by distressing and uncomfortable emotions that can disrupt a person's sense of equilibrium, manifesting as tension, restlessness, fear, nervousness, sweating, and related symptoms. The objective of this study is to examine the impact of Taizé meditation on anxiety levels. Methods: This study utilized a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 99 individuals, and 33 participants were selected through purposive sampling. The instrument used was the Depression Anxiety Stress Scales (DASS)-42, specifically the 14-item anxiety subscale. Data were analyzed using the Paired T-Test. Results: The average anxiety score prior to Taizé meditation was 3.73, which decreased to 1.76 after the intervention. Statistical analysis using the Paired T-test revealed a p-value of <0.001 (p < 0.05), indicating a significant difference. Conclusion: These findings suggest that Taizé meditation has a significant effect on reducing anxiety levels. Students are encouraged to practice Taizé meditation independently as a strategy to manage anxiety.